Analysis of Soil Nutrition Analysis with HART Protocol a Review - Singh, Ayushi; Mishra, Abhishek; Ahmed, Mohammed (International Journal of Computer Sciences and Engineering, 2019)
The IoT, the idea of getting real-world objects connected with each other, will change the way users arrange, get and expend data drastically. IoT empowers different applications (crop development observing and determination, water system choice help, and so on) in Digital Agriculture domain. Wireless HART is modern network protocols in WSNs which system of multiple small sensors (nodes), limited energy sources, used to sense any given sensing region (environment) of interest. Nodes in HARTs are provided with low power and are employed in a hazardous environment where replacement of the battery or any fault evaluation in the sensor network is impossible. With the help of this approach which gives continuous data about the terrains and harvests that will enable ranchers to settle on right choices.